Delivery of Telomerase Reverse Transcriptase Small Interfering RNA in Complex with Positively Charged Single-Walled Carbon Nanotubes Suppresses Tumor Growth - Zhang, Zhuohan; Yang, Xiaoying; Zhang, Yuan; Zeng, Bin; Wang, Shujing; Zhu, Tianhui; Roden, Richard B.S.; Chen, Yongsheng; Yang, Rongcun (Clinical cancer research, 2006)
Purpose: To determine whether -CONH-(CH 2 ) 6 -NH 3 + Cl − functionalized single-walled carbon nanotubes (SWNT) carrying complexed small interfering RNA (siRNA) can enter into tumor cells, wherein they release the siRNA to silence the targeted gene. Experimental Design: -CONH-(CH 2 ) 6 -NH 3 + Cl − was used to mediate the conjugation of telomerase reverse transcriptase (TERT) siRNA to SWNTs. The ability of TERT siRNA delivered via SWNT complexes to silence the expression of TERT was assessed by their effects on the proliferation and growth of tumor cells both in vitro and in mouse models. Results: The functionalized SWNTs -CONH-(CH 2 ) 6 -NH 3 + Cl − could facilitate the coupling of siRNAs that specifically target murine TERT expression to form the mTERT siRNA:SWNT+ complex. These functionalized SWNTs rapidly entered three cultured murine tumor cell lines, suppressed mTERT expression, and produced growth arrest. Injection of mTERT siRNA:SWNT+ complexes into s.c. Lewis lung tumors reduced tumor growth. Furthermore, human TERT siRNA:SWNT+ complexes also suppressed the growth of human HeLa cells both in vitro and when injected into tumors in nude mice. Conclusions: -CONH-(CH 2 ) 6 -NH 3 + Cl − functionalized SWNTs carry complexed siRNA into tumor cells, wherein they release the siRNA from the nanotube sidewalls to silence the targeted gene. The -CONH-(CH 2 ) 6 -NH 3 + Cl − functionalized SWNTs may represent a new class of molecular transporters applicable for siRNA therapeutics.